Evaluation of POMP for Filariasis and Factors Associated with Its Problems in East Manggarai Regency in 2017 - Fransiskus Salesius Onggang (Health Notions, 2018)
Filariasis (elephantiasis) is a chronic infectious disease caused by filarial worms and transmitted by Mansonia, Anopheles, Culex, and Armigeres mosquitoes. The worm lives in the canal and lymph nodes with acute clinical manifestations of recurrent fever and lymph node inflammation. This disease is one of the serious public health problems in Indonesia. Almost all regions of Indonesia are filariasis endemic areas, especially in Eastern Indonesia which has a higher prevalence. The provision of mass drugs for filariasis needs to be evaluated for the sustainability of treatment programs for the following year, so that an efficient and effective treatment program model can be found. The purpose of this study was to evaluate the implementation of POMP (Giving Mass Medicines for Prevention) for Filariasis and the factors associated with its success in East Manggarai Regency. The study was conducted in East Manggarai Regency in 2017, with a qualitative approach, using a mixed method, in order to evaluate the success of mass treatment in East Manggarai Regency. Research subjects were family heads who had taken medication, health officers, community leaders, religious leaders, and managers of filariasis control programs; selected by purposive sampling technique. The data collected includes monitoring and evaluation, partnerships, drug availability, drug distribution, the ability of health workers, the presence of health workers, the negative effects of taking medicine, and government policies. Data were collected through interviews and FGDs, then analyzed descriptively with a qualitative approach the results showed that the success of POMP was 83%, with problems namely drug distribution was not evenly distributed, implementation of uneven treatment, monitoring of side effects of drugs was not complete, type of drug was incomplete, frequency of treatment was not regulated, and funding policy support from legislative institutions did not yet exist. Keywords: Evaluation, POMP for filariasis, Filariasis elimination